Application of Evidence-Based Nursing Practice Benson Relaxation in Cancer Patients Undergoing Chemotherapy to Reduce Nausea and Improve Sleep Quality: Case Report: Penerapan Evidence – Based Nursing Practice Relaksasi Benson Pada Pasien Kanker Yang Menjalani Kemoterapi Terhadap Penurunan Mual Dan Peningkatan Kualitas Tidur: Case Report - Ikhtiarani, Inggil; Aprianti, Tutty (Journal of Health and Cardiovascular Nursing, 2023)
Nasopharyngeal cancer is a type of malignancy that is common  found cancer in Indonesia. One of the medical treatments for cancer is chemotherapy, the effects occur decreased sleep quality. An intervention reduce nausea and improve sleep quality in chemotherapy patients is Benson relaxation. This research aims to apply Evidence Based Nursing Practice Benson's relaxation to reduce nausea and improve sleep quality in cancer patients using "Effect of Benson's Relaxation Response on Sleep Quality and Anorexia in Cancer Patients Growing Chemotherapy: A Randomized Controlled Trial" as the main journal. This research is case report was conducted on one nasopharyngeal cancer patient who underwent Benson relaxation for 5 consecutive days, 2 sessions a day with a duration of 10 to 15 minutes. Results were obtained if the patient experienced a decrease in nausea and an increase in sleep quality as measured using VAS/NRS to measure nausea. and SMHSQ (ST Mary Hospital Sleep Questionnaire) to measure sleep quality in cancer patients. This article refers to another health workers to apply Benson relaxation to cancer patients with symptom of nausea, sleep disorders, anxiety and pain.